A NEW MULTIDISCUS ? SPECIES (FORAMINIFERA) FROM A FUSULINACEAN-RICH SUCCESSION ENCOMPASSING THE CARBONIFEROUS-PERMIAN BOUNDARY IN THE HADIM NAPPE (CENTRAL TAURUS, TURKEY) (Rivista italiana di Paleontologia e Stratigrafia, 1999)
The Hadim Nappe Carboniferous-Permian boundary and its fusulinacean-rich strata from the Çatalkatran Tepe stratigraphic section were studied. The appearance of Sphaeroschwagerina sp. determines the Carboniferous-Permian boundary in this section. The presence of Pseudofusulina ? buzulukensis Dobrokhotova, Pseudofusulina parviflucta Zhou, Pseudofusulina hovunensis Davydov, Occidentoschwagerina (?) kosvaensis Echakov and Rugosofusulina stabilis Rauzer-Chernousova confirm the Asselian age. A new Multidiscus ? species, Multidiscus ? tauridiana n. sp. was discovered from the Early Permian (Asselian) of Turkey (Hadim Nappe, Central Taurus).